Evaluasi Efektivitas Pengendalian Internal pada Aktivitas Outsourcing Pengelolaan Bea Meterai - Furqan, Furqan; Hartanti, Dwi (Politeknik Ganesha Medan, 2024)
Stamp duty is the only type of tax that is managed by the Directorate General of Taxes (DJP) through the outsourcing mechanism. Under this mechanism, the management of stamp duty is predominantly carried out by third parties, while the DJP acts as the principal overseeing the process. As previously researched, despite its advantages, the outsourcing mechanism also comes with weaknesses and risks. Therefore, controls are needed to ensure they align with the DJP's intended objectives. This research aims to evaluate the effectiveness of the internal controls implemented by the DJP in the outsourcing activities related to stamp duty management. The study takes the case study form and adopts a qualitative approach, evaluating the components and principles of the 2013 COSO Internal Control Integrated Framework concerning outsourcing activities in stamp duty management. Data collection involves document analysis and interviews with individuals directly involved in stamp duty management. The data is analyzed using maturity levels to determine the effectiveness of each control component and principle. The research results reveal diverse levels of control effectiveness. Among the five control components, only two are at an optimum level, while the others exhibit lower levels of effectiveness in control principles. This study provides recommendations to the DJP for enhancing internal control effectiveness, particularly in the aspects of supervising the internal control system, comprehensively identifying risks, and considering the potential for fraud in risk assessments. This research is expected to contribute academically and serve as a reference for regulators in making decisions related to stamp duty management.